Determination of Informal Sector as Urban Pollution Source : Fume Characterization of Small-scale Manual Metal Arc Welding using Factor Analysis in Bandung City - A. Nastiti; D.Y. Pramudyastuti; K. Oginawati; M. Santoso (Atom Indonesia, 2012)
In developing countries, the informal sector, particularly small-scale welding activities, are considered to be an important contributor to urban air pollution although studies in this sector are limited. This study aims to identify the composition of small-scale welding fume in order to further investigate the effects and set control strategies and urban pollution abatement policies. Breathing zone air samples were collected from 30 mild steel manual metal arc welders and 17 non-welders in Bandung City, West Java, Indonesia. The respirable particulates in air samples were analyzed using gravimetric method, and Instrumental Neutron Activation Analysis (INAA) was employed to identify characteristic of welding fume. It was found that respirable particulates concentration in welders (range : 315.6 and 3,735.93 µgm-3; average 1,545.436 µgm-3) were significantly higher than in non-welders (range : 41.84 and 1,688.03 µgm-3; average : 375.783 µgm-3). Welders’ breathing zones contain Fe>Na>K>Mn>Al >Cr>Ti>Cl>Br>I>Zn>Sb>V>Co>Sc; while non-welders’ breathing zones contain Cr>F>Al>Ti>Na>Br>I>Mn>Cl>Co>Zn>Sc. Inter-species correlation analysis conducted using Statgraphic Ver. 4.0 shows that Fe (range : n.d. – 775.19 µgm-3; average: 0.1674 µgm-3), Co (range : n.d. – 0.51 µgm-3; average: 0.000082 µgm-3), Mn (range : 0.39 – 148.37 µgm-3; average: 0.0374 µgm-3), Na (range: 0.17 and 623.85 µgm-3; average: 0.0973 µgm-3) and K (range : n.d. – 301.15 µgm-3; average: 0.0535 µgm-3) were emitted from welding activity, and thus are considered as components of welding fume which contribute to urban air pollution. Although welding fume and the identified species in welding fume were still below permissible limit, small-scale welding activities have great potential in emitting higher fume concentration due to due to high variability of welding activities, such as welding frequency, materials being welded, and varied environmental conditions.Received: 5 December 2011; Revised: 17 April 2012; Accepted: 20 April 2012